OTULIN haploinsufficiency predisposes to environmentally directed inflammation - Staels, Frederik; Bücken, Leoni; De Vuyst, Leana; Willemsen, Mathijs; Van Nieuwenhove, Erika; Gerbaux, Margaux; Neumann, Julika; Malviya, Vanshika; Van Meerbeeck, Lize; Haughton, Jeason; Seldeslachts, Laura; Gouwy, Mieke; et al. (Frontiers in Immunology, 2024)
Recently OTULIN haploinsufficiency was linked to enhanced susceptibility to S. aureus infections accompanied by local necrosis and systemic inflammation. The pathogenesis observed in haploinsufficient patients differs from the hyperinflammation seen in classical OTULIN-Related Autoinflammatory Syndrome (ORAS) patients and is characterized by increased susceptibility of dermal fibroblasts to S. aureus alpha toxin inflicted cytotoxic damage. In vitro immunological abnormalities were not observed in OTULIN haploinsufficient patients, suggesting a non-hematopoietic basis. In this research report, we investigated an Otulin+/- mouse model after in vivo provocation with lipopolysaccharide (LPS) to explore a potential role of hematopoietic driven inflammation in OTULIN haploinsufficiency. We observed a hyperinflammatory signature in LPS-provoked Otulin+/- mice, which was driven by CD64+ monocytes and macrophages. Bone marrow-derived macrophages (BMDMs) of Otulin+/- mice demonstrated higher pro-inflammatory cytokine secretion after in vitro stimulation with LPS or polyinosinic:polycytidylic acid (Poly:IC). Our experiments in full and mixed bone marrow chimeric mice suggests that the observed inflammation was mainly driven by the hematopoietic compartment with cell-extrinsic effects likely contributing to inflammatory outcome. Using an OTULIN haploinsufficient mouse model, we validated a role for OTULIN in the regulation of environmentally-directed inflammation.